Respuestas

  • Usuario de Brainly
2013-05-31T03:18:11+02:00
f (x) = x² -3x+1
f (-1) =(-1)² - 3(-1) + 1 → f(-1) = 5
f (-3) = (-3)² - 3(-3) + 1 → f(-3) = 9 + 9 +1→f(-3) = 19
f (3) =
(3)² - 3(3) + 1 → f(-3) = 9 - 9 +1→f(3) = 1
f (a-1) = (a-1)² - 3(a -1) + 1→ f(a-1) = a² - 2a +1 -3a +3 + 1→f(a-1) =a²- 5a + 5
f (a-1) = Repetida con la anterior
f (t²) = (t²)² - 3(t²) + 1→f(t²) = t^4 - 3t² + 1
f (-z) = (-z)² - 3(-z) + 1→f(-z) = z² + 3z + 1
f (az) = (az)² - 3(az) + 1→ f(az) = a²z² - 3az + 1

espero que te sirva,salu2!!!!